NSI reports: Supporting Australian healthcare governance. Issue 4 (April 2017) - Robertson, Jennifer; Mitchell, Marion; Moss, Sandra; Casey, Veronica
Abstract : Delve into a nurse-sensitive indicator pilot project, which yielded standardized electronic reports to ease healthcare management "down under."